(3cJGH YQhS GdCaQGM aj TQM JdNjU GdeaJGMs - (3GdSHcj, CMeO Hf Ydj Hf YHO GdcGaj,s 719-763 (3g`(B.s; (3GdbRhjfj, eMeO Hf YHO GdQMef Hf YeQ,s 666-739 (3g`(B.s; (3GdScGcj, jhSa Hf CHj HcQ Hf eMeO,s 555-626 (3g`(B.s ((3HjQhJ (B:s (3GdecJHI GdYUQjI,s, 2003)
(3jJfGhd GdHdGZI GdYQHjI(B.s
Keywords: (3GddZI GdYQHjIs -- (3HdGZIs